(untitled) (International Journal of Physiotherapy, 2017)
Background: Expert athletes in archery can rapidly achieve postural stability compared to beginners and novice athletes. This study investigated the effectiveness of a core stability training program in reducing the postural sway among adolescent archers. Methods: Participants (n=12) of this study were aged between 13-18 years; were divided into two groups (i.e., experimental and control). The experimental group underwent a supplementary eight-week core stability training program apart from their regular training program. Data were collected at three-time points; pre, after four weeks and post-training. Postural sway was measured in the anteroposterior plane and medio-lateral plane – center of pressure (CoP). Results: Mixed factorial ANOVA yielded significant interactions over time in the performance of the push up; plank; archery performance and postural sway. Postural sway between the experimental and control group was significantly different on both planes at T2; (CoP range x - F(1,10) = 7.952, p <.05, d = 1.302; CoP range y - T2; F(1,10) = 7.887, p<.05). The results were replicated at T3; CoP range x - F(1,10)= 7.952, p <.05; CoP range y - F(1,10)= 11.105, p <.05). Conclusion: The experimental group showed a smaller range in postural sway on both axes; indicating a reduction in the postural sway. A significant relationship was also evident between CoP range x, CoP range y and the participants’ performance in archery. It is recommended that a core stability training program is incorporated into an archery training program for adolescent archers.